Universal Social Values in the Perspective of Sayyid Husain Fadhlullah's Thematic Tafsir - Moh. Hafidul Ahkam; Ahmad Fawaid (al-Afkar, Journal For Islamic Studies, 2026)
Increasing global social tensions, identity conflicts, and humanitarian crises highlight the urgency of reconstructing universal ethical values grounded in the Qur’an. However, existing studies tend to be normative and lack contextual integration with contemporary social realities. This study aims to analyze the construction of universal social values in the thematic interpretation of Sayyid Muhammad Husain Fadlullah and examine its relevance to modern social challenges. This research employs a qualitative library approach using thematic (maudhu‘i) interpretation and qualitative content analysis, supported by a hermeneutic framework. The primary source is Tafsir Min Wahy al-Qur’an, complemented by relevant academic literature. The findings reveal that Fadlullah constructs an integrated system of social ethics consisting of justice (al-‘adl), human dignity (karamat al-insan), social solidarity (al-takaful al-ijtima‘i), and diversity (al-ta‘addudiyyah). These values are interrelated and function as a dynamic, contextual, and transformative ethical framework. The study concludes that Fadlullah’s interpretation contributes significantly to developing a universal, inclusive, and applicable social ethics framework for plural and modern societies.